Rastreio da água da rede de abastecimento da cidade de Guarabira - PB - Silva, Higo Braga da (2020)
This work has the objective to track water distributed in a distribution network supplied by four sources using the EPANET hydraulic simulation model. The case study comprises the water supply system in the city of Guarabira - PB. After the execution of the hydraulic modeling in EPANET, it was possible to use the tracer tracking tool to identify the percentages of water originating in each reservoir for each node in the network at times of maximum and minimum demand. With the results generated from the tables extracted from the EPANET program, it was possible to draw a new map of the influence of the reservoirs in the water distribution network of the city of Guarabira for these times. With the definition of the sectors, among other benefits, it will be possible for the city water concession company to improve this model and use it when there is a need to intervene in any part in the network. The conclusive results of this work demonstrated, through the computational tool used, what the operators of the supply system in the city of Guarabira already observed in practice. The influences of each reservoir on the supply of the main nodes in the supply network was proven.